EMPIRICAL INVESTIGATION OF THE UNDERPRICING PHENOMENON ON IPOs IN PRIVATIZATION OF SOEs: EVIDENCE FROM INDONESIA - Monika Setiobudi; Dezie L. Warganegara; Doni S. Warganegara (Journal of Applied Finance & Accounting, 2011)
The Objective this empirical research is conducted with the main purpose to assess whether the short-run underpricing level of IPOs on privatization is lower or not compared to the privately owned enterprises in Indonesia. The aim is intended to identify whether the presence of excessive underpricing is occurred among the Privatization IPOs in Indonesia. Method are used to fullfil the objective, the samples are derived from both SOEs and Non-SOEs that conducted the Initial Public Offerings (IPO) during period 2000-2009. The total final samples used are 147 samples. Moreover, this research focuses on the initial return of the first trading day to determine the underpricing level. The data is also analyzed by using descriptive statistics, Kolmogorov Smirnov test, parametric tests, Non-parametric tests and Multiple Regression Analysis. Result of the research shows the evidence that the extent of underpricing is significantly lower in IPOs conducted by the SOEs compared to the privately owned in Indonesia. Furthermore, the result also clarifies that there is no occurrence of excessive underpricing within the Privatization IPOs in Indonesia.Conclusion is the degree of underpricing within the SOEs is proven to be lower than the Non-SOEs. This fact is supported by the reasons of tight standardize legislation, underwriter’s reputation, budget deficit in Indonesia, and well-established industry within the SOEs.